Perceived Barriers to Leisure-Time Physical Activity Among Physically Active Individuals With Spinal Cord Injury - Paul K. Watson, BAppSci; Laura Stendell, MPhysio; Camila Quel De Oliveira, PhD; James W. Middleton, MBBS, PhD; Mohit Arora, PhD; Glen M. Davis, PhD (Archives of Rehabilitation Research and Clinical Translation, 2024)
Objective: To investigate barriers to leisure-time physical activity (LTPA) for physically active people with spinal cord injury (SCI). Design: Prospective cross-sectional. Setting: General community. Participants: One hundred and five physically active individuals with SCI. Interventions: Semi-structured interviews and surveys. Main Outcome Measure: Participants were surveyed and interviewed to determine barriers and determinants of LTPA participation. SCI-specific physical activity (PA) guideline adherence was documented. Barriers were categorized using the capability, opportunity, motivation, and behavior model, and regression statistics were used to determine relationships between LTPA volume and barriers. Results: Health problems, costs of equipment and programs, pain, and a lack of energy were the most common capability barriers, and a lack of accessible facilities, confidence in the knowledge and skill of a health professional, and a lack of time were common opportunity barriers. Motivation barriers pertained to self-consciousness in a fitness center and a lack of interest. Believing LTPA to be too difficult, uninteresting, and unable to improve health emerged as significant barriers to SCI-specific PA guideline adherence. Conclusion: SCI-specific PA guideline adherence was below 50% in physically active individuals. There are still numerous capability and opportunity barriers that physically active people with SCI must overcome when engaging in LTPA. Motivational barriers such as feeling self-conscious in a fitness center significantly influence PA guideline compliance in this population. Service providers should emphasize the benefit of LTPA to people with SCI while providing LTPA options that facilitate enjoyment, interest, and inclusivity, particularly for those who do not meet PA guideline recommendations.